Vim stimulation as a predictor of response to deep brain stimulation in patients of severe tremor undergoing dual stimulation (Translation: The University of Toledo Journal of Medical Sciences, 2018)
Deep brain stimulation, targeting the ventral intermediate nucleus of the thalamus (Vim), has been shown to be an effective management tool for tremors refractory to other therapies. There is some variance in response to Vim stimulation for severe essential and rubral tremors. This study looked at dual stimulations (addition, in which the Vim is stimulated along with an additional nucleus or augmentation, in which a second lead is placed within the Vim itself) for these types of tremors. A total of eight patients, four with rubral and four with severe essential tremors, were treated with deep brain stimulation. The responses of the patients were characterized on a scale from excellent improvement to worsening of condition. Two of the four patients with rubral tremor had an excellent response to Vim stimulation. These patients showed additional benefits when the prelemniscal radiation (Raprl) was stimulated, in addition to the Vim. Three of the four patients with severe essential tremor reported either a good or excellent response to Vim stimulation. One of these patients had the Raprl stimulated in addition to the Vim while another had an augmentation of the Vim, with ventralis oralis posterior (Vop) stimulation. Both showed additional benefits with the addition or augmentation performed. We conclude that if a patient with severe medically refractory tremor (essential or rubral tremor) responds to Vim stimulation but is still disabled he will likely also have a response to dual stimulation with an additional lead in the Raprl or an augmentation with an additional lead in the Vop. Patients who did not initially respond to Vim stimulation did not respond to the placement of a second lead. We also conclude that for severe essential tremor, Raprl stimulation showed a better response than Vim stimulation.
Keywords: tremor; Vim; Voa; Vop; Raprl; newer targets; multiple targets